2002
DOI: 10.1021/ol026791m
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Synthesis of the Polypropionate Subunit of Callystatin A Based on Regioselective Internal Alkyne Hydrostannation

Abstract: [formula: see text] An improved route to the polypropionate segment of callystatin A is described in which the efficient directed hydrostannation of an internal alkyne and subsequent iodinolysis provides a key vinylic iodide intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Reaction with the primary propargylic acetate 61 followed by iodination gives the alkenyl iodide 62 in 81% overall yield (Scheme 90). 168 A palladium-catalyzed hydrostannation of alkynyl esters 91,169,170 is used in a synthesis of 4-alkylidenebutenolactone 65, a substructure of the carotenoids pyrrhoxanthin and peridinin. It is suggested that in addition to electronic polarization of the acetylenic bond, the presence of the neighboring isopropylidenedioxy group in 63 is responsible for the formation of the single stereo-and constitutional isomer 64 (Scheme 91).…”
Section: Applications To Synthesismentioning
confidence: 99%
“…Reaction with the primary propargylic acetate 61 followed by iodination gives the alkenyl iodide 62 in 81% overall yield (Scheme 90). 168 A palladium-catalyzed hydrostannation of alkynyl esters 91,169,170 is used in a synthesis of 4-alkylidenebutenolactone 65, a substructure of the carotenoids pyrrhoxanthin and peridinin. It is suggested that in addition to electronic polarization of the acetylenic bond, the presence of the neighboring isopropylidenedioxy group in 63 is responsible for the formation of the single stereo-and constitutional isomer 64 (Scheme 91).…”
Section: Applications To Synthesismentioning
confidence: 99%
“…This product was further manipulated to obtain the necessary vinyl iodide 53, which coupled with another segment under Suzuki-coupling conditions to finish (À)callystatin A (Scheme 12). [43] In a similar way, the four stereocenters in the polypropionate marine defense substance (À)-membrenone C were introduced by a sequence involving the addition of chiral allenylmetal reagents to aldehydes, which was followed by a double intramolecular hydrosilylation/oxidation process to install the b-hydroxy ketone subunits, and a double intramolecular aldol reaction to finalize the total synthesis (Scheme 13). [44] Diastereoselective hydroboration of allenylstannane with diisopinocampheylborane [( d Ipc) 2 BH] at À40 to À20 8C followed by a kinetically controlled highly diastereoselective 1,3-boratropic shift afforded chiral allylborane 54.…”
Section: Marshall Et Al Completed the Syntheseis Of Leptostatinsmentioning
confidence: 99%
“…If racemization occurred at the allenyl-Pd intermediate, any product formed would be racemic because racemization must necessarily occur before the transmetalation/reductive elimination step. Therefore, the Pd(II) racemization mechanism remains a possibility with NaOP(O)(OEt) 2 or NaHCO 3 playing the role of LiBr; however, no experimental evidence for this proposal has been gathered. Furthermore, this mechanism seems unlikely due to the weakly nucleophilic character of the phosphate or bicarbonate anions compared to bromide in the reported example.…”
Section: Probing the Stereospecificity Of The Reaction -Optimization mentioning
confidence: 99%